2016
DOI: 10.1111/pce.12761
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic conductance and the maintenance of water balance in flowers

Abstract: Flowers face desiccating conditions, yet little is known about their ability to transport water. We quantified variability in floral hydraulic conductance (Kflower ) for 20 species from 10 families and related it to traits hypothesized to be associated with liquid and vapour phase water transport. Basal angiosperm flowers had trait values associated with higher water and carbon costs than monocot and eudicot flowers. Kflower was coordinated with water supply (vein length per area, VLA) and loss (minimum epider… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(138 citation statements)
references
References 64 publications
5
129
4
Order By: Relevance
“…According to physical principles and experimental evidence, regulating the atmospheric moisture was an efficient solution for suppressing the excess driving force. The mass of plant water transport through the plant must balance the transpiration losses from the leaves, which can be expressed as follows1516:…”
Section: Discussionmentioning
confidence: 99%
“…According to physical principles and experimental evidence, regulating the atmospheric moisture was an efficient solution for suppressing the excess driving force. The mass of plant water transport through the plant must balance the transpiration losses from the leaves, which can be expressed as follows1516:…”
Section: Discussionmentioning
confidence: 99%
“…For example, the water costs of flowers can limit flower size and impede leaf function (Galen, ; Galen, Sherry, & Carroll, ; Lambrecht, ; Lambrecht & Dawson, ; Teixido & Valladares, , ). This requirement of maintaining water balance has led to coordinated shifts in hydraulic traits that vary systematically across the angiosperm phylogeny (Roddy, Brodersen, & Dawson, ) and with other pollination traits, such as floral lifespan (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Flower maintenance may require a considerable amount of water (Roddy and Dawson, 2012) and, under dry conditions, those plants can lose more water from their flowers than from the leaves (Lambrecht, 2013). Therefore, understanding the physiological mechanisms of floral water transport and water relations may provide new insights into the evolution of flowers (Galen, 2000; Chapotin et al, 2003; Feild et al, 2009a,b; Roddy et al, 2016). Even though water has an essential role throughout the floral lifespan, few studies have focused on water relations in flowers (Feild et al, 2009b; Lambrecht et al, 2011; Roddy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the physiological mechanisms of floral water transport and water relations may provide new insights into the evolution of flowers (Galen, 2000; Chapotin et al, 2003; Feild et al, 2009a,b; Roddy et al, 2016). Even though water has an essential role throughout the floral lifespan, few studies have focused on water relations in flowers (Feild et al, 2009b; Lambrecht et al, 2011; Roddy et al, 2016). Contrasting results in different species have indicated that some flowers are phloem-hydrated (Trolinder et al, 1993; Chapotin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%